Bibliometric Profile of Refereed Articles Published in Anatolia: Journal of Tourism Research - Dönüş Çiçek; Nazmi Kozak (Türk Kütüphaneciliği)
Anatolia: Journal of Tourism Research first went under the name of Anatolia: Journal of Tourism and Environment at 1990. Journal published academic chronicles between 1990-1997, after 1997 changed to refereed journal. The aim of this study is to analyze and compare refereed articles in three year periods (1997-2001, 2002-2006, 2007-2011) in some parameters. According to the findings of 202 articles, maximum article (72 articles) was published in the first period (1997-2001). Results showed that; first period’s popular subject was ‘tourism’, second period’s (2002-2006) popular subject was ‘tourism marketing’ and the third period’s (2007-2011) popular subject was ‘tourism management’. As an interdisciplinary science, multi-authored articles increased in the second period. First period’s maximum contribution was by doctorates, second and third period contributions were by assistant professors. These findings are important of indicating the 15 years development of Anatolia Journal, which significantly contributes tourism literature.